Thy-1 (CD90), Integrins and Syndecan 4 are Key Regulators of Skin Wound Healing - Pérez, Leonardo A.; Leyton, Lisette; Valdivia, Alejandra (Frontiers in Cell and Developmental Biology, 2022)
Acute skin wound healing is a multistage process consisting of a plethora of tightly regulated signaling events in specialized cells. The Thy-1 (CD90) glycoprotein interacts with integrins and the heparan sulfate proteoglycan syndecan 4, generating a trimolecular complex that triggers bi-directional signaling to regulate diverse aspects of the wound healing process. These proteins can act either as ligands or receptors, and they are critical for the successful progression of wound healing. The expression of Thy-1, integrins, ands syndecan 4 is controlled during the healing process, and the lack of expression of any of these proteins results in delayed wound healing. Here, we review and discuss the roles and regulatory events along the stages of wound healing that support the relevance of Thy-1, integrins, and syndecan 4 as crucial regulators of skin wound healing.